The Mobilization of Title IX across U.S. Colleges and Universities, 1994-2014. (28th March 2018) - Reynolds, Celene
Abstract: Title IX has been widely recognized as a crucial step toward gender equality in America. Yet, it remains unclear how the law actually functions, particularly how it has been used in response to gender disparities in higher education. This article provides the first systematic analysis of how Title IX has been mobilized at the postsecondary level. Drawing on new data acquired through seven Freedom of Information Act requests, I analyze all resolved Title IX complaints filed with the Office for Civil Rights against four-year nonprofit colleges and universities from 1994 to 2014. I find that the mobilization of Title IX has changed both in frequency and in kind during this period. Filings started to rise after 2000 and exploded after 2009, while sexual harassment complaints nearly equaled academic and athletic filings for the first time in 2014. Private, more selective institutions as well as schools located in states with more women serving in state legislatures face a disproportionate number of complaints relative to enrollment, indicating the importance of institutional context to legal mobilization.